(Re)creating objects from the past - affect, tactility and everyday creativity - Vachhani, Sheena J. (Management & organizational history : M&OH, 2013)
In this paper I explore the notion of everyday creativity as affective practice through the resurrection of craft, especially vintage objects and traditional craft practices that evoke memories of objects from the past. This is explored in relation to two specific sites of organization: (1) knitting culture through the practice of yarn bombing; and (2) the resurrection of vintage objects such as vinyl record collecting. These two sites form powerful and contrasting creative contexts, yet they are also connected in that they creatively modify cultural and physical landscapes. Taking the affective turn as the basis of the discussion, I explore ways in which tactility and touch intersect with everyday creativity to provide meaning and self-identity but also affective relationships with objects. Thus, the contribution of this paper develops a neglected area of affect and its relation to consumer cultures, especially cultures of making and collecting that constitute experience of forgotten pasts in organization studies. I conclude by discussing the affective politics of craft and the resurrection, reproduction and recreation of vintage objects.